Pengaruh Kepercayaan dan Kepuasan terhadap Loyalitas Nasabah Perbankan Syariah - Wahyuni, Endang Tri (Akmenika: Jurnal Akuntansi dan Manajemen, 2015)
This study aims to determine the influence of trust and satisfaction both partially and simultaneously to customer loyalty. This study took 60 customers as the respondent sample, the sample was taken by purposive sampling technique. Data analysis using the multiple linear regression. The results showed that the variable of trust (X1) had a partially positive and significant effect on customer loyalty (Y), that is proved by the results of statistical t value of 5,599 with a significance value of 0,000 < 0,05. Satisfaction variable (X2) had t value of 3,748 with a significance value of 0,000 < 0,05, this the satisfaction variable (X2) had a positive and significant influence on consumer loyalty (Y). The results of the f test was 36,991 and the significance value was 0,000. These results proved that simultaneously the variable of trust and satisfaction had positive and significant influence on customer loyalty.